Higher Price, Lower Costs? Minimum Prices in the EU Emissions Trading Scheme. (20th February 2019) - Abrell, Jan; Rausch, Sebastian; Yonezawa, Hidemichi
Abstract: In this paper, we examine the introduction of a price floor in an emissions trading system (ETS) when some emissions are regulated outside the ETS. We theoretically characterize the conditions under which a price floor enhances welfare. Using a numerical simulation model of the European Union (EU), we find that moderate minimum prices in the EU ETS can reduce the costs of EU climate policy by up to 30 percent. We also find that, because of tax‐interaction effects, the optimal minimum price in the EU ETS should be about four times higher than the average marginal abatement cost in non‐ETS sectors.